Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1016/s0736-0266(00)00080-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue reactions to particles of bone‐substitute materials in intraosseous and heterotopic sites in rats: discrimination of osteoinduction, osteocompatibility, and inflammation

Abstract: Two rat models were used to characterize tissue-specific reactions to particles of bone-substitute materials: one for osteocompatibility in a healing tibial wound and the other in a heterotopic, subcutaneous site. Small, unicortical tibial wounds in rats healed spontaneously, beginning with the rapid proliferation of intramedullary woven bone. That temporary bone was resorbed by osteoclasts and finally, the cortical wound was healed with lamcllar bone and the medullary space was repopulated with marrow. When v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 32 publications
2
33
0
6
Order By: Relevance
“…In the present study, specimens from all three experimental groups failed to demonstrate the presence of osteoinduction, and this is in agreement with a number of other studies which reported a lack of osteoinduction following implantation of HA-TCP into experimental animals [23,27,28].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, specimens from all three experimental groups failed to demonstrate the presence of osteoinduction, and this is in agreement with a number of other studies which reported a lack of osteoinduction following implantation of HA-TCP into experimental animals [23,27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Although the uncoated Straumann® Bone Ceramic material was not osteoconductive, another HA/TCP preparation, Zimmer, demonstrated an osteoconductive capacity similar to previously described [17]. Similar findings of heterogeneity amongst HA-TCP preparations have been reported [55,56].…”
Section: Discussionsupporting
confidence: 81%
“…Bone graft is generally considered to be the most successful bone filling material because of its osteoconductive, osteoinductive and osteogenic properties [14,21,23,31,41]. Nevertheless, autograft harvesting involves increased operative time and the donor site morbidity, while allograft has lower osteoinductive properties and carries disease transmission risk.…”
Section: Debated Issuesmentioning
confidence: 99%